Avoiding Plagiarism: A Guide for Students - Abdullah, Nor Azni; Muhammad, Ahmad Mazli; Krishnakumari A/P N. R., Krishnan (Institute of Quality & Knowledge Advancement (InQKA), UiTM, 2012)
Everyone has heard of the word "plagiarism", and most people think they know what it means. A simple definition of plagiarism is: Copying the words or ideas of someone else and using them in your own writing without indicating that the words/ideas were copied or borrowed and without indicating where they were copied from. In other words, it means that you present another person's work as if it was your own work. Although some students plagiarise because they are lazy, other students plagiarise because they do not know how to show that they are using other people's words or ideas. When you were at school, you wrote essays on general topics "out of your head", from your general knowledge. If you were asked to write for a project or portfolio, you probably copied directly from books or cut-and-pasted material you found on the Internet. Your teachers may have warned you not to plagiarise, but they probably did not teach you what to do, and you probably did not get penalised if you did copy directly from somewhere else. However, at university, the situation is very different; plagiarism is considered a very serious matter. At UiTM, penalties for plagiarism range from having marks deducted, to failing a course, to suspension from classes. This guide will give you step-by-step instructions to show you how to use words and ideas from reference sources in your academic writing, without plagiarising.